THEORETICAL BACKGROUND OF PERIPHERAL NERVOUS SYSTEM STUDY: CRANIAL NERVES - Tarasenko, Ya.A. (World of Medicine and Biology, 2014)
Oral presentation of teaching material at higher educational institutions (HEIs) presupposes mainly the use of verbal methods of teaching. Among them a lecture is of primary importance. The word “lecture” comes from Latin lect-, meaning “read, chosen”. Lectures provide with systematized fundamentals of scientific knowledge, disclose the state and prospects of the development of corresponding branch of science and technology, focus on the most complicated and main issues, stimulate the learners’ active cognitive activity and facilitate the development of creative thinking. Even at the age of state-of-the-art information technologies lectures remain one of the leading means of study at medical HEI. The detailed study of the anatomy of peripheral nervous system is crucial for future physicians regardless of their specialty.The lecture aims at eliciting the specific characteristics of the structure, topography and innervation zone of cranial nerves. Some publications often use the term “craniocerebral nerves”. According to the latest anatomical terminology, approved in San-Paolo in 1997, the term is denominated as Nervi craniales, i.e., cranial nerves. They are numbered by the Roman numerals based on their rostral-caudal orientation; each of them has their own denomination. The olfactory and optic nerves arise from the base of the forebrain, consisting from axons of nerve cells, located in the nasal cavity mucosa (olfactory organ) or in the retina. The other sensory nerves are formed by eviction from the developing cerebrum of young nerve cells, which processes form sensory nerves or sensory (afferent) fibers of mixed nerves. Motor cranial nerves have been arisen from the motor (efferent) nerve fibers, which are the processes of motor nucleus cells, occupying the brain stem. The formation of cranial nerves in phylogenesis is connected with the development of visceral arches and their derivatives, sense organs and reduction of somites in the head area. The lecture presents the topographic features of twelve pairs of cranial nerves and describes innervation zones. Specific instrumental approaches are applied for more scrutinous study of some cranial nerves. State-of-the-art ophthalmological equipment provides with detailed data about the eye ground and optic disc condition, its trophism; to define the boundaries of field of view and focal prolapses in it; computerized methods of study of visual evoked potentials make it possible to detect visual analyzer disorder of various localization. Craniography is used to study the optic and acoustic canals. This method provides with evaluation of state of superior orbital fissure, round, ragged, jugular and other foramens. Vertebral and carotid angiography is of specific diagnostic value in terms of identification of bulky cranial process and vascular malformations, leading to compression or deformity of cranial nerves. However, the more informative is computer tomography, providing with visualization of specific stems of cranial nerves; diagnostics of acoustic or optic nerve neoplasm and other lesions of cranial nerves. Methods of somatosensory cortical evoked potentials are used to study the functions of trigeminal nerve, auditory stem evoked potentials, i.e., functions of vestibulocochlear nerve.
Keywords: peripheral nervous system; cranial nerves; lecture